2013
DOI: 10.2147/jaa.s14743
|View full text |Cite
|
Sign up to set email alerts
|

Lung penetration and patient adherence considerations in the management of asthma: role of extra fine formulations

Abstract: The mainstay of management in asthma is inhalation therapy at the target site, with direct delivery of the aerosolized drug into the airways to treat inflammation and relieve obstruction. Abundant evidence is available to support the concept that inflammatory and functional changes at the level of the most peripheral airways strongly contribute to the complexity and heterogeneous manifestations of asthma. It is now largely accepted that there is a wide range of clinical phenotypes of the disease, characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 55 publications
(58 reference statements)
0
31
0
2
Order By: Relevance
“…In a cohort of patients aged ≥65 years, Soriano et al [32] reported an association between asthma and diseases of different organ systems (especially cardiac and respiratory). Moreover, in elderly patients, unintentional non-adherence to inhalation therapy represents a complex problem often related to comorbidities requiring multiple medications [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of patients aged ≥65 years, Soriano et al [32] reported an association between asthma and diseases of different organ systems (especially cardiac and respiratory). Moreover, in elderly patients, unintentional non-adherence to inhalation therapy represents a complex problem often related to comorbidities requiring multiple medications [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…The full dose feedback system provides accurate dose metering and consistent full dose release independently of the inspiratory flow. (18,19) NEXThaler has a unique ''open-inhaleclose'' operating sequence that is at least one inhalation step less than that of other existing DPIs and easy for patients to use. Complex operating systems requiring several handling steps can increase the chance of making an error and lead to unintentional nonadherence of patients using their medication.…”
Section: Discussionmentioning
confidence: 99%
“…NEXThaler Ò (Chiesi Farmaceutici S.p.A.) is a DPI with an innovative full dose feedback system incorporating a novel breath-actuated mechanism (BAM): a click is heard and a dose counter decreases by one count, only after effective full dose delivery. (18,19) NEXThaler Ò provides a high lung deposition throughout the entire bronchial tree (56% of the emitted dose in patients with asthma), (19,20) and the BAM is activated at a consistent inhalation flow that is independent of disease severity and the level of asthma control, i.e., 35.0 and 35.4 L/min in patients with controlled and partially controlled/uncontrolled asthma, respectively. (21,22) At the time of writing this article (October 2013), NEXThaler is marketed in Germany, Spain, and The Netherlands, and has been approved in the following countries: Austria, Belgium, Bulgaria, Greece, France, Hungary, Italy, Luxembourg, Poland, Slovenia, and Slovakia.…”
mentioning
confidence: 99%
“…It has also been demonstrated that Foster ® NEXThaler ® emits a high fraction of fine (diameter < 5 μm) and extrafine (diameter < 2 μm) particles (Buttini et al, 2016) with high lung deposition efficiency and a more uniform deposition distribution . The special internal design and structure of the inhaler is considered to contribute to the above characteristics of the drug (Scichilone et al, 2013). The most innovative feature of the device is the built in BAM (breath-actuated mechanism).…”
Section: Introductionmentioning
confidence: 99%